2015
DOI: 10.1080/07347332.2015.1067279
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Psychosocial Mediators, and Cognitive Mediators in Parents of Child Cancer Patients and Cancer Survivors: Attention and Working Memory Pathway Perspectives

Abstract: Evidence of stress on attention and working memory processes in parents of child cancer survivors is insufficiently developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 143 publications
0
13
0
4
Order By: Relevance
“…In a previous review focused on analyzing different studies related to the effects of stress on cognition in parents of children with cancer, an important effect of this variable on cognitive tasks such as attention or working memory was observed. These effects are also related to the development of pathologies such as depression or anxiety associated with children's illness [50]. We must take into account that in our study, the mean age of the CCG was 48.95 years and the mean age of the patients was 52.41 years and, therefore, results obtained could be difficult to compare with prior studies carried out with younger subjects.…”
Section: Discussionmentioning
confidence: 86%
“…In a previous review focused on analyzing different studies related to the effects of stress on cognition in parents of children with cancer, an important effect of this variable on cognitive tasks such as attention or working memory was observed. These effects are also related to the development of pathologies such as depression or anxiety associated with children's illness [50]. We must take into account that in our study, the mean age of the CCG was 48.95 years and the mean age of the patients was 52.41 years and, therefore, results obtained could be difficult to compare with prior studies carried out with younger subjects.…”
Section: Discussionmentioning
confidence: 86%
“…Sixty-four systematic reviews were excluded for the following reasons: not a clinical or at-risk population (n=22), not a systematic review (n=20), primary aim was not to review mechanisms (n=21), and non-M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT human sample (n=1). Finally, 54 systematic reviews met the inclusion criteria and were included in the overview[18,19,[28][29][30][31][32][33][34][35][36][37]20,[38][39][40][41][42][43][44][45][46][47]21,[48][49][50][51][52][53][54][55][56][57]22,[58][59][60][61][62][63][64][65][66][67]23,[68]…”
mentioning
confidence: 99%
“…Studies on parental stress in both cardiac and non-cardiac populations have shown that mothers and fathers perceive stress and react to stressors differently. 26,32,37,[43][44][45][46][47][48][49] The majority of research has shown that mothers score significantly higher on stress and anxiety measures. 9,17,26,46 For parents of children with CHD, mothers have been shown to have significantly higher distress, anxiety, depression, and somatisation compared with fathers.…”
Section: Sexmentioning
confidence: 99%